Research on the Power Consumed by Drives of Machines for Working with Greenhouse Soil (Global Journal of Science Frontier Research, 2024)
The quality of soil preparation for greenhouses is a key factor influencing crop yields in organic farming Several machines perform various operations for working with greenhouse soil a soil removal machine a loader-mixer for soil components and a machine for laying soil components Theoretical research has established that the greatest influence on the power of the component laying machine comes from the speed of the conveyor chain the angular velocity of the dosing drum the number of conveyor scrapers and the number of drum slats For the power of the soil removal machine the influencing factors are the size of the cut soil layer the speed of the machine itself and the angle of the bucket surface Experimental research confirmed the results of theoretical studies and established the parameter values of the combined layer that minimize power consumption conveyor chain speed 0 33-0 37 m s number of conveyor scrapers 7-8 angular velocity 6 0-6 5 rad s and the number of dosing drum slats 6 For the soil removal machine these parameters are bucket angle 25-27 degrees forward speed 0 2-0 25 m s and the size of the cut soil layer 0 18 m The presented results confirm the effectiveness of the machinery complex for greenhouse soil preparation
Keywords: power; regression equation; graphical dependency; combined layer; machine for removing and loading greenhouse soil